Design and Building of an Automatic Water Filling System on Water Container Media Based on Arduino Esp8266 - Pradana, Alfazri Putra; Aminudin, Nur; Rizki, Fahlul; Feriyanto, Dwi (IJOEM Indonesian Journal of E-learning and Multimedia, 2024)
In the era of rapidly developing technology, innovation is important to facilitate human life. Water is the main need for all living things, especially humans, so it needs to be managed efficiently. Water filling in reservoirs is usually still done manually, which can cause a waste of clean water. Manual water filling requires humans to control the pump as needed. However, it often happens to forget to turn off the pump after the reservoir is full, which can cause a waste of water and electrical energy. To solve this problem, the idea is to make an automatic system with Arduino ESP 8266 called "Design of Automatic Water Filling System on Arduino ESP 8266 Based Water Reservoir". This system uses ultrasonic sensors to measure the water level in the reservoir. When the water reaches a certain level, the system will activate the water filling, and the user can monitor the water level in real time through a mobile device. This research aims to design and test this automatic water replenishment system to avoid water waste. The result is expected to be an efficient solution better than the manual system and beneficial in clean water management. This research will answer important questions about this system's design, workings, and test results. The main conclusion of this research is the need for improvements in the design and implementation of automatic water filling systems. Further analysis, adjustments, and retesting are needed to overcome the obstacles encountered.